Personality and Perception : Assessing the Role of CEO Narcissism in Risk Disclosure Practices in an Emerging Market - Rajabalizadeh, Javad (Sage, 2026)
This study investigates the impact of CEO narcissistic traits on risk disclosure within Iran's corporate governance framework, analyzing 1,480 firm-year observations from Tehran Stock Exchange-listed companies (2013–2022). We measure CEO narcissism by the size of signatures on annual reports and assess risk disclosures using a specialized bag-of-words model for Persian Management Discussion and Analysis (MD&A) documents. Our results reveal a significant positive relationship between CEO narcissism and the extent of risk disclosures, supporting theories of Self-Promotion and Visibility Enhancement. These findings are validated through sensitivity analyses that adjust for variations in narcissism measurements across different time periods and CEO tenures, alongside recalculating model standard errors with various clustering methods. Further tests across business, operational, and financial risk dimensions consistently show the positive impact of CEO traits on corporate risk communication. We employ firm fixed effects, apply entropy balancing, and focus on periods of CEO transitions to address potential biases and endogeneity concerns. Additionally, our analysis explores the moderating role of board composition, which significantly interacts with CEO narcissism to affect disclosure practices. The post-2015 regulatory environment is also analyzed as a moderator, highlighting that regulatory changes amplify the influence of narcissistic traits on disclosures. Employing established methodologies corroborates these findings, further demonstrating the profound effect of CEO traits on corporate risk communication in a non-Western context. This research enhances understanding of how leadership traits influence corporate transparency and risk disclosure.